Cervical Artery Dissection. Issue 2 (April 2023) - Omran, Setareh Salehi
ABSTRACT: OBJECTIVE: Cervical artery dissection is a common cause of stroke in young adults. This article reviews the pathophysiology, etiology and risk factors, evaluation, management, and outcomes of spontaneous cervical artery dissection. LATEST DEVELOPMENTS: Cervical artery dissection is believed to be a multifactorial disease, with environmental factors serving as possible triggers in patients who have a genetic predisposition to dissection formation. Cervical artery dissection can cause local symptoms or ischemic events, such as ischemic stroke or transient ischemic attack. Neuroimaging is used to confirm the diagnosis; classic findings include a long tapered arterial stenosis or occlusion, dissecting aneurysm, intimal flap, double lumen, or intramural hematoma. Patients with cervical artery dissection who present with an acute ischemic stroke should be evaluated for IV thrombolysis, endovascular therapy eligibility, or both. Antithrombotic therapy with either anticoagulation or antiplatelet treatment is used to prevent stroke from cervical artery dissection. The risk of recurrent ischemia appears low and is mostly limited to the first two weeks after symptom onset. ESSENTIAL POINTS: Cervical artery dissection is a known cause of ischemic strokes. Current data show no difference between the benefits and risks of anticoagulation versus antiplatelet therapy in the acute phase of symptomatic extracranial cervical artery dissection, thereby supporting the recommendation that clinicians can prescribe either treatment. Further research is warranted to better understand the pathophysiology and long-term outcomes of cervical artery dissection.